LAW OF THE INTERNAL MARKET OF THE EUROPEAN UNION - Sead Mehovic (Journal of Bio-Based Marketing)
The internal market represents a crucial aspect of the EU, characterized by the free movement of goods, services, people, and capital without internal borders. This market is underpinned by fundamental market freedoms, which are essential for promoting economic growth and cooperation among member states. The legislative processes have evolved to streamline decision-making, addressing inefficiencies caused by complex procedures. The Lisbon Treaty formalized the co-decision process, making it the regular legislative procedure within the EU. Legal frameworks governing the internal market comprise both primary and secondary laws. The primary law includes foundational treaties such as the Treaty on European Union and the Treaty on the Functioning of the European Union, which facilitate economic activity among member states. Secondary law encompasses regulations, directives, and decisions that regulate the market’s functioning. Ultimately, the establishment of the internal market and its legal structure aims to create an environment that fosters economic integration while protecting fundamental rights. Through its legal institutions, particularly the Court of Justice of the EU, the Union safeguards these rights, ensuring that the principles of justice and equality are upheld within the context of an integrated European economy.